Non-linear waves of plastic deformation and criteria of quasi-ductile fracture; Физическая мезомеханика; Т. 7, № Спец1 - Egorushkin V. E. (2004, 2004)
The new approach to the development of criteria of quasiductile fracture is proposed based on the theory of nonlinear waves of localized inelastic deformation. It can be applied to consideration of quasiductile fracture of materials where the dislocation contribution to fracture can be disregarded (nanomaterials, surface hardened solids, thin films etc.)